2019
DOI: 10.1029/2019sw002367
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nearly Frontal and Highly Inclined Interplanetary Shocks on High‐Latitude Field‐Aligned Currents (FACs)

Abstract: We present high-latitude field-aligned current (FAC) response to nearly frontal shocks (NFSs) and highly inclined shocks (HISs) through a superposed epoch analysis. The FACs are derived from magnetic perturbation data provided by the Active Magnetosphere and Planetary Electrodynamics Response Experiment program. Forty-nine events for each group are used for the superposed epoch analysis. The 25%, 50%, and 75% quantiles of the FAC and total current distributions are studied. We found that NFSs are statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 52 publications
14
18
0
Order By: Relevance
“…By carefully analyzing two isolated substorms triggered by similarly strong shocks with very different inclinations, we found that the general geomagnetic activity represented by geomagnetic indices, energetic particle injection, auroral poleward expansion, westward auroral electrojet current, ground dB/dt variations, and ULF wave activity following the NFS were overall higher than the same effects following the HIS. These findings are supported by many experimental (Oliveira et al, 2016(Oliveira et al, , 2020Oliveira & Raeder, 2015;Shi et al, 2019;Takeuchi et al, 2002;Wang et al, 2006) and simulation (Guo et al, 2005;Oliveira & Raeder, 2014;Samsonov, 2011;Samsonov et al, 2015;Selvakumaran et al, 2017) works in the literature.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…By carefully analyzing two isolated substorms triggered by similarly strong shocks with very different inclinations, we found that the general geomagnetic activity represented by geomagnetic indices, energetic particle injection, auroral poleward expansion, westward auroral electrojet current, ground dB/dt variations, and ULF wave activity following the NFS were overall higher than the same effects following the HIS. These findings are supported by many experimental (Oliveira et al, 2016(Oliveira et al, , 2020Oliveira & Raeder, 2015;Shi et al, 2019;Takeuchi et al, 2002;Wang et al, 2006) and simulation (Guo et al, 2005;Oliveira & Raeder, 2014;Samsonov, 2011;Samsonov et al, 2015;Selvakumaran et al, 2017) works in the literature.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, these observations also indicate that both NFS and HIS were similarly strong events, but with different inclinations. These results are supported by many simulations and observations of shocks impinging the magnetosphere with different orientations (Guo et al, 2005;Oliveira & Samsonov, 2018;Shi et al, 2019;Wang et al, 2006).…”
Section: Magnetopause Standoff Positionsupporting
confidence: 76%
“…Numerical simulations show that shocks with small impact angles usually lead the MI system to faster and stronger responses in comparison to shocks with large impact angles (Guo et al, 2005;Oliveira & Raeder, 2014;Samsonov et al, 2015). These results have been confirmed by many experimental studies as well (Oliveira & Raeder, 2015;Oliveira, Arel, et al, 2018;Rudd et al, 2019;Shi et al, 2019;Takeuchi et al, 2002;Wang et al, 2006;Xu et al, 2020). Oliveira and Raeder (2014) studied the effects caused by shock orientations on the Earth's magnetosphere through numerical simulations.…”
Section: 1029/2020gl090857mentioning
confidence: 83%
“…We use the SuperMAG dataset because the SuperMAG indices are usually more likely to capture geomagnetic activity triggered by shocks due to their larger and more effective geographic coverage (e.g. Oliveira et al, 2016;Oliveira & Raeder, 2015;Oliveira & Samsonov, 2018;Rudd et al, 2019;Shi et al, 2019;Oliveira et al, 2020).…”
Section: Ground-based Magnetic Field and Image Datamentioning
confidence: 99%
“…Consequently, when shocks hit Earth, different levels of geomagnetic activity may follow, including ground sudden impulses, field-aligned current and auroral intensifications, and wave response in the magnetosphere-ionosphere system (e.g., see review by Oliveira & Samsonov, 2018). Observations and simulations show that geomagnetic activity following the impact of an inclined shock is usually weaker and slower than the geomagnetic activity following a frontal shock as a result of asymmetric magnetospheric compressions (Takeuchi et al, 2002;Guo et al, 2005;Grib & Pushkar, 2006;Wang et al, 2006;Samsonov, 2011;Samsonov et al, 2015;Selvakumaran et al, 2017;Shi et al, 2019;Xu et al, 2020). Numerical simulations conducted by Oliveira and Raeder (2014) showed that a frontal shock triggered intense substorm activity, whereas an inclined shock triggered moderate substorm activity, even though the inclined shock was stronger.…”
Section: Introductionmentioning
confidence: 99%